Statin Induced Changes in Rat Pancreatic Tissue: A Histological and Biochemical Perspective - Abdullah Qamar; Hammad Gul Khan; Muhammad Marghoob Khan; Muhammad Rizwan Bashir Kiani; Hina Kundi; Fareeha Mushtaq (Journal of Rawalpindi Medical College)
Objective: This study aimed to elucidate the effects of simvastatin on pancreatic histomorphology and biochemical profile in a rat model.